O isolamento social e o trabalho remoto na pandemia de covid-19 em uma universidade pública na região Centro-Oeste do Brasil: o trabalho feminino representado por elas - Katiuscia Kintschev (2023)
The woman, as a result of the social structure rooted in patriarchal ideology, has always faced inequalities in working conditions, evidenced primarily by studies on the burden of women's work and the overlap of domestic work and work in the public sphere. Considering the outbreak of the COVID-19 pandemic between 2020 and 2022, questions arise about the implications for social representations of women's working conditions resulting from biosafety measures such as social distancing and remote work, for a group of female employees at a public university. Thus, the present study seeks to analyze the social representations of domestic and paid work during the COVID-19 pandemic for a group of female employees. It is a descriptive study with qualitative analysis, based on data from the "Corona and Mental Health Project - UFMS in the Midwest". Data collection involved individual interviews using a semi-structured script with participants from the first phase of the mentioned research. Data organization utilized content analysis technique, following L. Bardin's reference, to identify the significant elements of social representations present in the interviews conducted with participants who were working women during the period of social distancing. The results indicate the existence of an antagonistic duality, as the interviewees initially claim that there is no differentiation between male and female work, but subsequently bring up the issue of the female obligation to manage, care for, and maintain the home and family. Thus, in the discourse and actions of the women studied, there is a perpetuation of the burdened woman's position, who combines the roles of "homemaker" and "successful professional woman," even in a scenario of a childless couple where a more balanced division of the invisible work (domestic chores) could be achieved between the individuals living and isolated at home during the period of social isolation.